Effects of BP-14, a novel cyclin-dependent kinase inhibitor, on anaplastic thyroid cancer cells - Allegri, Lorenzo; Baldan, Federica; Mio, Catia; Puppin, Cinzia; Russo, Diego; Kryštof, Vladimir; Damante, Giuseppe (Oncology reports, 2016)
Anaplastic thyroid carcinoma (ATC) is an extremely aggressive human malignancy characterized by a marked degree of invasiveness, absense of features of thyroid differentiation and resistance to current medical treatment. It is well known that ATCs are characterized by deregulation of genes related to cell cycle regulation, i.e., cyclin-dependent kinases (CDKs) and endogenous cyclin-dependent kinase inhibitors (CDKIs). Therefore, in the present study, the effect of a novel exogenous cyclin-dependent kinase inhibitor, BP-14, was investigated in three human ATC cell lines. The ATC-derived cell lines FRO, SW1736 and 8505C were treated with BP-14 alone or in combination with the mTOR inhibitor everolimus. In all ATC cell lines, treatment with BP-14 decreased cell viability and, in two of them, BP-14 modified expression of genes involved in epithelial-mesenchymal transition. Thus, our data indicate that BP-14 is a potential new compound effective against ATC. Combined treatment with BP-14 and the mTOR inhibitor everolimus had a strong synergistic effect on cell viability in all three cell lines, suggesting that the combined used of CDK and mTOR inhibitors may be a useful strategy for ATC treatment.
Keywords: Gene Expression Regulation, Neoplastic; everolimus; viabilita buněk; 2-Aminopurine; Everolimus; Cell Line, Tumor; Antineoplastic Combined Chemotherapy Protocols; Epithelial-Mesenchymal Transition; regulace genové exprese u nádorů; Thyroid Neoplasms; Cell Survival; 2-aminopurin; Drug Synergism; inhibitory proteinkinas; synergismus léků; nádory štítné žlázy; lidé; Humans; protokoly protinádorové kombinované chemoterapie; Protein Kinase Inhibitors; anaplastický karcinom štítné žlázy; Thyroid Carcinoma, Anaplastic; nádorové buněčné linie; epitelo-mezenchymální tranzice